Diffusion tensor magnetic resonance imaging in multiple sclerosis - Filippi, M; Cercignani, M; Inglese, M; Horsfield, M A; Comi, G (Neurology, 2001)
To quantify, using diffusion tensor imaging (DTI), the tissue damage in lesions and normal-appearing white matter (NAWM) from a large cohort of patients with MS and to investigate the magnitude of the correlation between DTI-derived metrics and clinical disability. Dual-echo and DTI scans were obtained from 78 patients with relapsing-remitting, secondary progressive, or primary progressive MS and from 20 normal control participants. Post-contrast T1-weighted images were also obtained from the patients. After creating mean diffusivity (D) and fractional anisotropy (FA) images and image coregistration, D and FA values were measured for 4846 lesions (3207 nonenhancing T1-isointense, 1511 nonenhancing T1-hypointense, and 128 enhancing), 497 NAWM areas from patients, and 160 white matter areas from the controls. The average lesion D was higher and the average lesion FA was lower than the corresponding quantities of the NAWM (p < 0.001). The values of enhancing and nonenhancing lesions were not different, whereas enhancing lesions had lower FA (p < 0.001). T1-hypointense lesions had higher D and lower FA than T1-isointense lesions (p < 0.001). NAWM of patients had higher and lower FA than white matter of controls (p = 0.01). Significant correlations were found between T1 and T2 lesion volume and and FA of lesions and NAWM. In the overall patient sample, a moderate correlation was also found between lesion D and the Expanded Disability Status Scale score (r = 0.28, p = 0.01). However, the r value of this correlation was 0.48 in patients with secondary progressive MS, whose disability was also correlated with average lesion FA (r = -0.50). The results of this study show that DTI is able to identify MS lesions with severe tissue damage and to detect changes in the NAWM. They also indicate that DTI-derived measures are correlated with clinical disability, especially in patients with secondary progressive MS, thus suggesting a role for DTI in monitoring advanced phases of the disease.